2006
DOI: 10.1111/j.1530-0277.2006.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance in Long‐Term Abstinent Alcoholic Individuals

Abstract: Background-There are few investigations of the potential recovery of neurocognitive function in chronic alcoholic samples after very long-term abstinence. The current study examined cognitive abilities in middle-aged, (mean age 46.8 years) long-term abstinent alcoholics (LTAA). Twenty-five LTAA men and 23 LTAA women abstinent for an average of 6.7 years were compared to an equal number of gender and age comparable normal controls (NC). We examined the association of neurocognitive variables with age, duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
127
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(146 citation statements)
references
References 41 publications
12
127
0
1
Order By: Relevance
“…Interestingly, the results of a recent cross-sectional study (Fein et al, 2006) indicated that most of the diffuse cognitive deficits observed in recently abstinent alcoholics abated in abstinent alcoholics with up to 13 years of sobriety to levels comparable to those of non-alcoholic controls. One notable exception was spatial capacities which appeared selectively vulnerable to long lasting impairment.…”
Section: Neurocognitive Characteristics Alcohol Use Patterns and Hementioning
confidence: 91%
“…Interestingly, the results of a recent cross-sectional study (Fein et al, 2006) indicated that most of the diffuse cognitive deficits observed in recently abstinent alcoholics abated in abstinent alcoholics with up to 13 years of sobriety to levels comparable to those of non-alcoholic controls. One notable exception was spatial capacities which appeared selectively vulnerable to long lasting impairment.…”
Section: Neurocognitive Characteristics Alcohol Use Patterns and Hementioning
confidence: 91%
“…These methodological shortcomings are important for our understanding of the effect of psychoactive substance abuse on cognition among patients with schizophrenia. This is especially true since the duration of substance abuse and length of abstinence are two factors that have been shown to influence cognition among substance abusers without psychotic disorders (Yucel et al, 2007;Fein et al, 2006;Pope, Gruber, & Yurgelun-Todd, 2001). Moreover, it will be important to evaluate, in the future, the influence of antipsychotics on cognitive performance in patients with dual disorders, since these patients are typically poorly compliant with medication (Negrete, 2003).…”
Section: Guidelines For Future Studiesmentioning
confidence: 96%
“…However, debate continues about the longer term pattern of change. Studies have demonstrated improvement in memory and executive function in the first months of abstinence [15] while others have found ongoing impairments in these domains [16,18], with deficits persisting for months or years after cessation of alcohol misuse [19]. or both of these conditions have improved.…”
Section: Introductionmentioning
confidence: 99%